SOCIO-ECONOMIC CONDITION OF GAMELAN CRAFTER IN WIRUN VILLAGE MOJOLABAN SUBDISTRICT SUKOHARJO DISTRICT 2019 - Maharani, Greti Regian; Sudargono, Agus; Rifa'i, Muh. Husyain (Journal of Geography Science and Education, 2019)
This study aims to find out: (1) The Socio-Economic Condition of Gamelan Craftsmen in Wirun Village, Mojolaban District, Sukoharjo Regency. (2) Level of Education of Gamelan Craftsmen in Wirun Village, Mojolaban Subdistrict, Sukoharjo Regency. (3) Distribution of Gamelan Home Industries and Gamelan Marketing Range in Wirun Village, Mojolaban District, Sukoharjo District.This study used qualitative descriptive, namely describing and knowing the socio-economic conditions of gamelan craftsmen in Wirun Village, the level of education of gamelan craftsmen in Wirun Village and knowing the distribution of the gamelan industry in Wirun Village and also the marketing range of the gamelan industry. The data collection techniques used are through field direct observation, interviews and documentation. Data analysis techniques used are analysis of descriptive data and table data.The results of this study are: (1) the socio-economic conditions of gamelan craftsmen totaling 26 craftsmen of all ages 15-64 years, the highest level of education is high school, the income level of 20 craftsmen ranges from 1,920,000-2,400,000, the number of family dependents is dominated by 3-5 people, the gamelan industry stands on average 10-50 years (2) The results of the highest education level of children at the level of high school / vocational and craftsman children are predominantly female. (3) The results of the spread of the gamelan industry are 6 industries and the majority of marketing reach the island of Bali. Keywords: distribution, gamelan, craftsmen